Tradeoffs and scaling of functional traits in Sphagnum as drivers of carbon cycling in peatlands. Issue 7 (25th February 2014) - Laing, C. G.; Granath, G.; Belyea, L. R.; Allton, K. E.; Rydin, H.
<x xml:space="preserve">Abstract</x> Growth and decomposition of Sphagnum controls turnover of a large global store of soil organic carbon. We investigated variation in morphological and physiological traits of Sphagnum shoots, and related this variation to canopy variables relevant to peatland carbon cycling. We sampled Sphagnum along a bog plateau‐swamp forest gradient and measured a suite of shoot traits and canopy variables. Major axes of variation were identified using principal component analysis and correlated with canopy variables such as growth, biomass and decomposition. We also examined scaling of shoot traits with one another and with canopy variables. Two distinct tradeoffs in shoot traits emerged. From dry to wet habitats, individual metabolic rates and capitulum size increased while numerical density decreased, leading to faster growth and elongation on an individual basis. From treed to open habitats, photosynthetic efficiency decreased and photosynthetic biomass increased, driving faster growth on an area basis and slower litter mass loss. The tradeoffs identified have important implications for peatlands undergoing climate‐related changes in water and light availability. Sphagnum trait comparisons, combined with scaling analyses, offer a promising approach to understanding and predicting the effects of environmental change on peatland carbon cycling.